2020
DOI: 10.1515/hsz-2019-0413
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 is modulated in pancreatic cancer cells under hypoxia and nutrient deprivation

Abstract: Pancreatic ductal adenocarcinoma is one of the most aggressive tumors with a microenvironment marked by hypoxia and starvation. Galectin-3 has been evaluated in solid tumors and seems to present both pro/anti-tumor effects. So, this study aims to characterize the expression of Galectin-3 from pancreatic tumor cells and analyze its influence for cell survive and motility in mimetic microenvironment. For this, cell cycle and cell death were accessed through flow cytometry. Characterization of inside and outside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 80 publications
2
2
0
Order By: Relevance
“…We demonstrated induction of LGALS3 gene expression in hypoxic BxPC3 cells and a trend towards increased expression in PANC-1 cells albeit not reaching statistical significance ( Figure 8 ). Our results are partially corroborated by an earlier study which showed LGALS3 expression in PANC-1 cells at 24h and 48h ( 88 ). Moreover, in the same year, Gonnermann et al.…”
Section: Discussionsupporting
confidence: 91%
“…We demonstrated induction of LGALS3 gene expression in hypoxic BxPC3 cells and a trend towards increased expression in PANC-1 cells albeit not reaching statistical significance ( Figure 8 ). Our results are partially corroborated by an earlier study which showed LGALS3 expression in PANC-1 cells at 24h and 48h ( 88 ). Moreover, in the same year, Gonnermann et al.…”
Section: Discussionsupporting
confidence: 91%
“…Gal-3 upregulation under hypoxic exposure has been reported for other tumors as breast (de Oliveira et al, 2015), thyroid (Zheng et al, 2017), and non-small-cell lung carcinoma (Kataoka et al, 2019). Previous results of our research group brought the upregulation of mRNA Gal-3 when PANC-1 cells undergone hypoxic incubation (da Silva Filho et al, 2020). The participation of Gal-3 in responses to extreme oxygen conditions seems to occur even in normal cells (Schunemann et al, 2007; Zeng et al, 2007; Doverhag et al, 2010).…”
Section: Discussionsupporting
confidence: 55%
“…A study by da Silva Filho et al . 49 investigated the modulation of Gal-3 in pancreatic cancer cells under hypoxia and nutrient deprivation conditions. The researchers observed that Gal-3 expression and secretion were increased in pancreatic cancer cells exposed to hypoxic conditions.…”
Section: Diagnostic Significancementioning
confidence: 99%